2015
DOI: 10.3390/nu7064938
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Protective Effects of Diosgenin against Doxorubicin-Induced Cardiotoxicity

Abstract: Doxorubicin (DOX) induces oxidative stress leading to cardiotoxicity. Diosgenin, a steroidal saponin of Dioscorea opposita, has been reported to have antioxidant activity. Our study was aimed to find out the protective effect of diosgenin against DOX-induced cardiotoxicity in mice. DOX treatment led to a significant decrease in the ratio of heart weight to body weight, and increases in the blood pressure and the serum levels of lactate dehydrogenase (LDH), creatine phosphokinase (CPK) and creatine kinase myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 58 publications
8
38
0
1
Order By: Relevance
“…Consistent to the results that we reported, Asfar et al also reported that doxorubicin treatment decreased the activities of antioxidant enzymes and Acacia hydaspica leaf extract that has the potential to increase GSH, GPx, and GR level which was attributed by polyphenolic constituents and antioxidant properties of this leaf extract [50]. A study done by Chen et al has shown that diosgenin, a steroidal saponin of Dioscorea opposita, also has the ability to increase the GSH and GPx level decreased by doxorubicin treatment in Balb/c mice [48]. ymoquinone, an active constituent of Nigella sativa, having antioxidant and anti-inflammatory actions was also shown to protect against doxorubicin-induced cardiotoxicity in mice with increased value of antioxidant markers including GSH, GPx, and GR activities [52].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 92%
See 1 more Smart Citation
“…Consistent to the results that we reported, Asfar et al also reported that doxorubicin treatment decreased the activities of antioxidant enzymes and Acacia hydaspica leaf extract that has the potential to increase GSH, GPx, and GR level which was attributed by polyphenolic constituents and antioxidant properties of this leaf extract [50]. A study done by Chen et al has shown that diosgenin, a steroidal saponin of Dioscorea opposita, also has the ability to increase the GSH and GPx level decreased by doxorubicin treatment in Balb/c mice [48]. ymoquinone, an active constituent of Nigella sativa, having antioxidant and anti-inflammatory actions was also shown to protect against doxorubicin-induced cardiotoxicity in mice with increased value of antioxidant markers including GSH, GPx, and GR activities [52].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 92%
“…According to the results of the present study, elevated AST and LDH levels were significantly reduced by the pretreatment with aqueous plant extract compared to the doxorubicin control. Many previous studies have also shown that compounds with antioxidant property may bring down the cardiac biomarkers in rats treated with doxorubicin [47][48][49].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 96%
“…Diosgenin, a bioactive steroid sapogenin from legumes and yams [1][2][3][4], has anticancer, cardiovascular protective, anti-diabetes, neuroprotective, immunomodulatory, estrogenic, and skin protective potency [1][2][3][4][5][6][7][8][9][10][11][12][13]. Moreover, diosgenin may foster male fertility [14].…”
Section: Introductionmentioning
confidence: 99%
“…Its effects may also be associated with the inhibition of topoisomerase II, free radical formation, and finally induction of the apoptosis process (Swift, Rephaeli, Nudelman, Phillips, & Cutts, ). DOX is most effective in the S and G2 phases of the cell cycle; its therapeutic utility is limited by cardiotoxicity (Chen, Wang, Hsu, Lin, & Chen, ) and nephrotoxicity (Su et al, ). Cellular injury induced by DOX may involve lipid peroxidation, changes in adenylate cyclase activity, and ROS formation (Chen et al, ), which finally leads to DOX‐induced apoptosis and inflammation.…”
Section: Triterpene Saponins and Doxorubicinmentioning
confidence: 99%
“…DOX is most effective in the S and G2 phases of the cell cycle; its therapeutic utility is limited by cardiotoxicity (Chen, Wang, Hsu, Lin, & Chen, ) and nephrotoxicity (Su et al, ). Cellular injury induced by DOX may involve lipid peroxidation, changes in adenylate cyclase activity, and ROS formation (Chen et al, ), which finally leads to DOX‐induced apoptosis and inflammation.…”
Section: Triterpene Saponins and Doxorubicinmentioning
confidence: 99%